Emotional self-regulation, virtual reality and neurofeedback - Joana Pinheiro (Elsevier, 2021)
The most common mental problems are anxiety disorders, affecting today about 264 million people in the world. The reference treatments present limitations, such as their side effects and long intervention periods. Recently, various approaches have emerged, such as neurofeedback, virtual reality and serious games. Objective: This study serves to determine preconditions and requirements for a game development, reusing virtual reality and neurofeedback to enhance the emotional self-regulation competences in individuals with anxiety disorders. Methods: a scoping review was performed to identify the serious games' characteristics, resourcing to neurofeedback existent in this scope; and a focus group to ascertain the specialists' more relevant perspectives about preconditions and requirements integrating a game with these characteristics and objectives. Results/conclusion: the scoping review results illustrate that the combined use of serious games, neurofeedback and virtual reality is still a very residual approach and without consolidated evidence, justifying the importance of further research. The specialists who formed the focus group emphasized, among others, the importance of gradual stimulation, co-creation and personalization of the developing resources.